2016
DOI: 10.1016/j.jallcom.2016.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Sb(Se,Te)I and photovoltaic applications

Abstract: SbXI (X=Se, Te) are ferroelectric semiconductors that allow a variety of applications including optoelectronic and photovoltaic applications. An analysis of the optical properties is carried out starting from first-principles density-functional theory with orbital-dependent one-electron potentials. To go into the contributions to the optical properties more deeply, the absorption coefficients have been split into inter-and intraspecies contributions and into atomic angular momentum contributions. The optical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 27 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Scanlon and co‐workers reported that BiSI and BiSeI possess electronic structures suitable for photovoltaic applications based on hybrid density functional theory. Using first‐principles density‐functional theory with orbital‐dependent one‐electron potentials, Tablero analyzed the optical properties of SbXI (X = Se, Te), demonstrating that these species are potential absorbents for photovoltaic devices. Sb 1− x Bi x SI is isostructural with the well‐known quasi‐1D ferroelectric SbSI and has attracted much attention because it shows many strongly coupled semiconductive and ferroelectric properties .…”
Section: Performance Of the Asbsi‐based Solar Cells Fabricated Using mentioning
confidence: 99%
“…Scanlon and co‐workers reported that BiSI and BiSeI possess electronic structures suitable for photovoltaic applications based on hybrid density functional theory. Using first‐principles density‐functional theory with orbital‐dependent one‐electron potentials, Tablero analyzed the optical properties of SbXI (X = Se, Te), demonstrating that these species are potential absorbents for photovoltaic devices. Sb 1− x Bi x SI is isostructural with the well‐known quasi‐1D ferroelectric SbSI and has attracted much attention because it shows many strongly coupled semiconductive and ferroelectric properties .…”
Section: Performance Of the Asbsi‐based Solar Cells Fabricated Using mentioning
confidence: 99%
“…Historically, bulk V-VI-VII compounds attracted tremendous interest in the 1960's due to promising ferroelectric properties [20][21][22][23][24][25] . The last five years have witnessed the renaissance of these materials for photovoltaic applications beyond perovskites [26][27][28][29][30][31][32][33] , because (i) orienting crystal growth perpendicular to the substrate sustains excellent carrier transport along the chains, (ii) benign grain boundaries parallel to the chains are free of dangling bonds and hence cause little recombination loss 34 , and (iii) needle-like crystals aligned in the translational direction of the growth exhibit better photovoltaic response than their higher dimensional counterparts 35 . For applications in field-effect transistors, the Achilles' heel of bulk V-VI-VII semiconductors is smaller band gap, lighter effective mass and much higher dielectric constant than 2D MoS 2 2,16,28,31 , which seriously reduces their potential.…”
mentioning
confidence: 99%
“…In contrast to common Pb and Sn, compounds containing trivalent Sb/Bi have ecological advantage and demonstrate good stability parameters in air [9]. Recently, SbTeI material was highlighted as relevant absorbent of the solar spectrum with high conversion efficiency evaluated from the theoretical absorption coefficients [10]. In addition, it shows low thermal conductance of the sheet which is favorable for 2D thermoelectric materials from the monolayer [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are only a few studies dealing with crystal structure of SbTeI and their results are quite different. This causes confusion, for example, when performing theoretical ab-initio calculations [10,[16][17][18]. Initially, it was announced that the structure may adopt the orthorhombic or even the lowest triclinic symmetry [19][20][21].…”
Section: Introductionmentioning
confidence: 99%